Comparative Study of Productivity of Organic and Conventional Agriculture in Maize Crops in East Java - Muhammad Hazmi; Dewa Oka Suparwata (Westscience Press, 2024)
This study provides a comparative analysis of the productivity of organic and conventional maize farming in East Java, employing a quantitative approach with 40 sample farms. Utilizing a Likert scale from 1 to 5, data were collected and analyzed using SPSS version 26. The findings indicate that while conventional farming demonstrates higher average yields, the difference in productivity between the two systems is statistically significant but not substantial. Organic farming shows competitive productivity, particularly in the long term, due to its positive impact on soil health and sustainability. The study highlights the potential of organic farming as a viable alternative to conventional practices in maize cultivation, offering valuable insights for policymakers and farmers in East Java.